Spinodal Copper Alloy C72900 - A New High Strength Anti-Friction Alloy System - W. R. Crib; F. C. Grensing (Canadian Institute of Mining, Metallurgy and Petroleum, 2010)
Copper-15 Nickel-8 Tin alloy is a relatively modern material, having been discovered in the 1970’s. It has complexities with casting, hot working and interdependent solid state phase transformations. A key to the high reliability manufacture of wrought rods, bars, plates and tube is the casting technology, which limits segregation, promotes microstructural uniformity and enables hot working. The EquaCast® continuous casting process has enabled the production of a broadening variety of wrought forms with typical yield strengths ranging from 100 to 180 ksi (690 to 1241 MPa) depending on size, shape and temper. This paper reviews the characteristics of wrought Copper-15 Nickel-8 Tin products which have registration in AMS specifications (4596 and 4597) and MMPDS-04 (CN-1) for use in aircraft. The design limits, microstructures, fracture characteristics and tribological behavior will be examined. This alloy system is emerging as a material of choice for aircraft bearings, corrosion resistant oil and gas exploration components, machinery and demanding off-road equipment applications. ToughMet® 3 is an alternative or upgrade to conventional moderate and high strength aluminum bronze bearing alloys.